The SAGE handbook of modern Japanese studies - Babb, James (Los Angeles SAGE Reference, 2015)
"The SAGE Handbook of Modern Japanese Studies includes outstanding contributions from a diverse group of leading academics from across the globe. This volume is designed to serve as a major interdisciplinary reference work and a seminal text, both rigorous and accessible, to assist students and scholars in understanding one of the major nations of the world."--from publisher's website
Part I. Land, history, and culture. Modern Japan in history / Andrew Cobbing -- Anthropology of modern Japan / Carolyn S. Stevens -- The practice of religion in Japan : an exploration of the state of the field / Lucia Dolce -- Mass media in Japan / Katja Valaskivi -- Heritage management in present-day Japan / Noriaki Nishiyama -- Geography's contributions to Japanese studies / Mary McDonald -- Regionalism and the local / Anthony Rausch -- Part II. Society. Education / Robert W. Aspinall -- Feminism / Vera Mackie -- 'How to sex'? The contested nature of sexuality in Japan / Mark McLelland -- Gender equity in Japan / Joyce Gelb -- Policing in Japan / David T. Johnson -- Organised crime / Peter Hill -- Part III. Medicine and health care. A brief history of Japanese medicine /Izumii Yokoyama and Michael D. Fetters -- Health care in Japan : excellent population health. low medical expenditures, yet ambiguous place of primary care / Jonathan E. Rodnick, Izumi Yokouyama and Michael D. Fetters -- Medical education in Japan / Michael D. Fetters and Izumi Yokoyama -- Bioethics and medico-legal issues in Japan / Michael D. Fetters -- Mental health in Japan / Denise St Arnault -- Part IV. Politics and foreign relations. Political 'science' and the study of Japanese politics / James Babb -- Parties and elections in Japan / Kenneth Mori McElwain -- Postwar democracy / Sherry Martin Murphy -- Civil society in Japan / Yuko Kawato, Robert J. Pekkanen and Hidehiro Yamamoto -- Japan's international relations / Christopher W. Hughes -- Japan and globalization / Hugo Dobson -- Japan-United States relations / Paul Midford -- Foreign relations with China / Caroline Rose -- Part V. Economy. The Japanese economy / Marcus Rebick -- Japanese business and management / Parissa Haghirian -- Japanese consumers and consumerism / Parissa Haghirian -- Labor relations / Akira Suzuki -- Foreign workers in Japan / Gabriele Vogt -- Agriculture / Aurelia George Mulgan -- Energy / Alexandru P. Luta and Paul Midford.
Includes bibliographical references and index.
Keywords: Japan -- Civilization; Japan -- Social conditions; Japan -- Economic conditions; Japan -- Politics and government